Narrative methods in quality improvement research. Issue 6 (2nd December 2005) - Greenhalgh, T; Russell, J; Swinglehurst, D
Abstract : This paper reviews and critiques the different approaches to the use of narrative in quality improvement research. The defining characteristics of narrative are chronology (unfolding over time); emplotment (the literary juxtaposing of actions and events in an implicitly causal sequence); trouble (that is, harm or the risk of harm); and embeddedness (the personal story nests within a particular social, historical and organisational context). Stories are about purposeful action unfolding in the face of trouble and, as such, have much to offer quality improvement researchers. But the quality improvement report (a story about efforts to implement change), which is common, must be distinguished carefully from narrative based quality improvement research (focused systematic enquiry that uses narrative methods to generate new knowledge), which is currently none. We distinguish four approaches to the use of narrative in quality improvement research—narrative interview; naturalistic story gathering; organisational case study; and collective sense-making—and offer a rationale, describe how data can be collected and analysed, and discuss the strengths and limitations of each using examples from the quality improvement literature. Narrative research raises epistemological questions about the nature of narrative truth (characterised by sense-making and emotional impact rather than scientific objectivity), which has implications for how rigour should be defined (and how it might be achieved) in this type of research. We offer some provisional guidance for distinguishing high quality narrative research in a quality improvement setting from other forms of narrative account such as report, anecdote, and journalism.